Моделирование процессов: учебное пособие - Кулешов В. К. Валерий Константинович; Корнев В. А. Вячеслав Андреевич; Дайчман И. В. Ирина Валерьевна; Шильникова Е. В. Елена Владимировна; Учайкина Е. С. Елена Сергеевна; Янушевская М. Н. Марина Николаевна (Томск, Изд-во ТПУ, 2013)
Заглавие с титульного экрана